KELAYAKAN ASPEK KEUANGAN TERHADAP BISNIS KERIPIK NANGKA PADA UD. WARNA SARI DI DESA SURANADI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - PERMADI, I GUSTI AGUNG DIDIT EKA; SYAFHARIAWAN, HERRY; EFENDI, HAYATI; SUARTHA, I DEWA GEDE (Universitas Mahasaraswati K. Mataram, 2023)
The aim of this research is to analyze the feasibility of the jackfruit chips business at UD. Warna Sari in Suranadi Village, Narmada District, West Lombok Regency financially. This research is applied research. The data collection method used in this research is the case method or often called a case study. The data collection techniques used in this research are observation, interviews and documentation. The data collection tools used in this research were questionnaires and cellphones (recorders). The conclusion obtained is that the results of the production of jackfruit chips must be sold by UD. The color of Sari in Suranadi Village, Narmada District, West Lombok Regency is 0.41 kg so that the business carried out does not experience losses and does not make a profit or is at the break-even point, the sales value of jackfruit chips is IDR 1.64, the total profit earned is IDR 13,597,570,- and the feasibility of the financial aspect of the jackfruit chips business is R/C > 1 of 4.49 for 30 production processes, which means that the jackfruit chips agro-industry business which has been running so far is worthy of development